Polycystic ovary syndrome: quantifying the psychosocial burden and the predictive role of sexual trauma history in clinical outcomes - Victor Manickam; Vedika Pillai (Frontiers in Endocrinology, 2026)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder that needs to be addressed through holistic management of metabolic, hormonal, and lifestyle factors. This research study, a cross-sectional examination, reports on clinical and psychological aspects of PCOS and PCOD in a group of 75 educated women analyzed with descriptive statistics, non-parametric tests, and binary logistic regressions. To carry out this analysis, we integrated the symptom severity index (SSI) and a binary measure of past sexual trauma history. The study observed irregular menstruation in 85.3% and weight gain in 84.0% of affected participants, representing a high prevalence of these core physical symptoms. The diagnostic status shows a psychological decline: post-diagnostic changes including feeling undesirable and being more introverted (p<0.001). Sexual molestation or abuse was reported by 72% of participants. Binary logistic regression showed that higher SSI scores (Odds Ratio = 1.72; 95% Confidence Interval [CI]: [1.28,2.30]; p<0.001) and a positive history of sexual trauma (OR = 3.58; 95% CI: [1.55,8.26]; p=0.003) were independent predictors of negative self-perception at diagnosis. The study argues that biomedical interventions are not enough and there needs to be a shift to integrated trauma-informed models of care. Human Design Education and Development can provide holistic support that promotes emotional inclusion by applying the principle of Listen and Share. In addition to reproductive and metabolic characteristics, PCOS/PCOD has a major psychological impact, which is clearly observed in this research of 75 educated women. There is a high symptom intensity and immediate decline in self-concept at diagnosis, which can result in negative body image and individuals feeling compelled to isolate themselves from society as a defense mechanism. This shows statistical significance (p=0.003). The number of people with higher symptom intensity and decline in self-concept due to negative body image and defensive social connection was recorded (p<0.001). Additionally, 72% of individuals self-reported sexual trauma, indicating a critical vulnerability that independently increased the likelihood of poor self-perception, irrespective of the intensity of physical symptoms (OR = 3.58, p=0.003).This study results in the immediate need for integrated trauma-informed multidisciplinary care paradigms in PCOS management and assesses the limitations of emphasizing interventions in biomedical management.